2014
DOI: 10.1002/cphc.201402147
|View full text |Cite
|
Sign up to set email alerts
|

Rules of Boron–Nitrogen Doping in Defect Graphene Sheets: A First‐Principles Investigation of Band‐Gap Tuning and Oxygen Reduction Reaction Catalysis Capabilities

Abstract: Introduction of defects and nitrogen doping are two of the most pursued methods to tailor the properties of graphene for better suitability to applications such as catalysis and energy conversion. Doping nitrogen atoms at defect sites of graphene and codoping them along with boron atoms can further increase the efficiency of such systems due to better stability of nitrogen at defect sites and stabilization provided by B-N bonding. Systematic exploration of the possible doping/codoping configurations reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Various theoretical studies on band gap engineering using h-BN and graphene mixtures, [15][16][17][18][19][20][21][22][23] have revealed the tuneability of these materials through the mixture of atoms. Other studies have focused on exploiting this tuneability for catalysis of oxygen reduction reactions, [24][25][26][27][28][29][30][31][32][33] water transport, 34 and H 2 adsorption. [35][36][37] An important aspect to consider, if using graphene and h-BN based materials as catalysts, is their degree of selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Various theoretical studies on band gap engineering using h-BN and graphene mixtures, [15][16][17][18][19][20][21][22][23] have revealed the tuneability of these materials through the mixture of atoms. Other studies have focused on exploiting this tuneability for catalysis of oxygen reduction reactions, [24][25][26][27][28][29][30][31][32][33] water transport, 34 and H 2 adsorption. [35][36][37] An important aspect to consider, if using graphene and h-BN based materials as catalysts, is their degree of selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles investigation of oxygen reduction reaction catalysis capabilities of As decorated defect graphene has shown that As adatoms adsorbed on double vacancy graphene system are very efficient and highly stable as an alternate Pt free oxygen reduction reaction(ORR) electrocatalyst [21]. Doping nitrogen atoms at defect sites of graphene and codoping them along with boron atoms can further increase the efficiency of such systems due to better stability of nitrogen at defect sites and stabilization provided by B-N bonding [22]. Recently sodium-ion batteries (SIBs) have drawn much attention over lithium ion batteries (LIBs) because of inexhaustible resources of sodium distributed evenly across the globe [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In one recent report 210 a large part of their work was devoted to an exhaustive study of boron, nitrogen, and B/N co-dopants on the double-vacancy (555-777) graphene surface. Their data indicate that a dopant structure with three boron atoms and seven nitrogen atoms, at the centre of the defect, was the most favourable in terms of formation energy.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…The influence of dopants on graphene surfaces with defects has been investigated by quantum chemical approaches 202,[207][208][209][210][211] . In one recent report 210 a large part of their work was devoted to an exhaustive study of boron, nitrogen, and B/N co-dopants on the double-vacancy (555-777) graphene surface.…”
Section: Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation